Congenital Hemolytic Anemias: Is There a Role for the Immune System? - Zaninoni, Anna; Fermo, Elisa; Vercellati, Cristina; Marcello, Anna Paola; Barcellini, Wilma; Bianchi, Paola (Frontiers in Immunology, 2020)
Congenital hemolytic anemias (CHAs) are a heterogeneous group of rare hereditary conditions including defects of erythrocyte membrane proteins, red cell enzymes, and disorders due to defective erythropoiesis. They are characterized by variable degree of anemia, chronic extravascular hemolysis, reduced erythrocyte life span, splenomegaly, jaundice, biliary lithiasis, and iron overload. Although few data are reported on the role of the immune system in CHAs, several immune-mediated mechanisms may be involved in the pathogenesis of these rare diseases. We reported in ~60% of patients with hereditary spherocytosis (HS), the presence of naturally-occurring autoantibodies (NAbs) directed against different membrane proteins (α-and β-spectrin, band 3, and dematin). Positive HS subjects showed a more hemolytic pattern and NAbs were more evident in aged erythrocytes. The latter is in line with the function of NAbs in the opsonization of damaged/senescent erythrocytes and their consequent removal in the spleen. Splenectomy, usually performed to reduce erythrocyte catheresis and improve Hb levels, has different efficacy in various CHAs. Median Hb increase is 3 g/dL in HS, 1.6-1.8 g/dL in piruvate kinase deficiency (PKD), and 1 g/dL in congenital dyserythropoietic anemias (CDA) type II. Consistently with clinical severity, splenectomy is performed in 20% of HS, 45% of CDAII, and in 60% of PKD patients. Importantly, sepsis and thrombotic events have been registered, particularly in PKD with a frequency of ~7% for both. Furthermore, we analysed the role of proinflammatory cytokines and found that interleukin 10 and interferon γ, and to a lesser extent interleukin 6, were increased in all CHAs compared with controls. Moreover, CDAII and enzymatic defects showed increased tumor necrosis factor-α and reduced interleukin 17. Finally, we reported that iron overload occurred in 31% of patients with membrane defects, in ~60% of CDAII cases, and in up to 82% of PKD patients (defined by MRI liver iron concentration >4 mg Fe/gdw). Hepcidin was slightly increased in CHAs compared with controls and positively correlated with ferritin and with the inflammatory cytokines interleukin 6 and interferon γ. Overall the results suggest the existence of a vicious circle between chronic hemolysis, inflammatory response, bone marrow dyserythropoiesis, and iron overload.